THE TRADITION OF "MUTER PUNDEN" AFTER THE MARRIAGE CONTRACT ON THE NORTH COAST OF PATI BASED ON THE PERSPECTIVE OF ISLAMIC LAW - Ahmad Amiruddin; Tali Tulab; Ahmad Zaenur Rosyid (Hukum Islam, 2023)
The research was conducted to find out the views of community leaders in Raci Village, Batangan Subdistrict, Pati Regency on the custom of circumambulating the punden after the marriage contract and to find out the law of circumambulating the punden after the marriage contract according to the perspective of Islamic law. This research uses a field research method (field risearch) with a normative sociological approach. The data collection techniques in this study come from primary data and secondary data obtained from observation, interviews and documentation. The results showed First, the view of the people of Raci Village, Batangan Subdistrict, Pati Regency on the tradition of circumambulating the punden after the marriage contract, must be carried out by every community with the intention of preserving traditions, honoring their ancestors and rejecting calamities. Secondly, in the perspective of Islamic Law, this marriage tradition is valid, because the conditions and pillars of marriage have been fulfilled. Because this custom is carried out after the validity of marriage and the custom of circumambulating the punden after marriage in Raci village and in terms of Ushul Fiqh methods is not included in 'Urf fasid, which is a custom that contradicts the arguments of Shara".